Development of an Ethno-STEM-Integrated Chemistry E-Module Based on Sleman Regency Local Wisdom for Reaction Rate Learning - Maulani, Dhina; Kristianingrum, Susila (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to develop a chemistry learning e-module based on the local wisdom of Sleman Regency integrated with Ethno-STEM for reaction rate learning. The novelty of this study lies in the systematic mapping of Sleman local culinary traditions into reaction rate concepts, including fermentation kinetics, catalyst activity, temperature effects, Maillard reactions, gelatinization, and surface-area-dependent processes. This study employed the Design-Based Research (DBR) model proposed by McKenney and Reeves, consisting of analysis and exploration, design and construction, and evaluation and reflection stages. The participants involved five chemistry teachers, 30 senior high school students, five peer reviewers, one material expert, and one media expert. Data were collected through needs analysis questionnaires, peer review sheets, expert validation instruments, teacher practicality questionnaires, and student readability questionnaires using a five-point Likert scale. The data were analyzed descriptively using average scores and ideal percentages. The developed e-module was presented as an interactive flipbook containing text, images, videos, hyperlinks, evaluations, and Live Worksheets activities. The results showed that the e-module achieved an ideal percentage of 95% in peer review (very good), 78% in material expert validation (good), and 98% in media expert validation (very good). Following revisions, the teacher practicality test and student readability test each obtained an ideal percentage of 96% (very good). Thus, the developed e-module was considered valid, practical, and highly readable for supporting contextual chemistry learning through the integration of local wisdom and the Ethno-STEM approach. However, this study was limited to validity, practicality, and readability evaluation and did not examine the effectiveness of the e-module on student learning outcomes.